Stress fractures - Current recommendations and principles for diagnosis and therapy Problemdiagnose Stressfraktur – Aktuelle Empfehlungen und Prinzipien zur Diagnostik und Therapie - Heiß, Rafael; Lutter, Christoph; Kastner, Tom; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo (Sport-Orthopädie, Sport-Traumatologie, 2022)
Stress fractures and stress reactions are among the injuries caused by overuse (“overuse injuries”) and can result in significant training and competition failures for affected athletes. Repetitive load effects that exceed the ability to cope with stress and adaptability, combined with intrinsic and extrinsic risk factors or tactical training errors, are considered to be the main cause of stress fractures. These and possible accompanying individual risk profiles are diverse and require complex and often interdisciplinary care. The majority of stress fractures heal easily and the recovery of full performance and resilience is usually given. However, if the diagnosis is delayed or inadequate (some injury entities require consistent decision-making regarding surgical therapy) or if secondary risk factors are not taken into account, prolonged healing processes, recurrent injuries or even multiple injury locations can occur at the same time. An early diagnosis and the beginning of a stage-appropriate therapy, including the consideration of existing risk factors, are therefore of essential importance.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Marching fracture; MRI; Running injury; Stress fracture; Stress reaction; X-ray